PENINJAUAN STATUS LINGKUNGAN EKSISTING SUNGAI MARIKINA, FILIPINA - Marwin Crispino; Eligia Clemente (ITB Journal Publisher, LPPM ITB, 2020)
Abstract: The physico-chemical characteristics of the Marikina River in an urban area of Metro Manila, Philippines was determined to evaluate the current degree of pollution. The study focused on one source at the site with general coordinates of 14°38'07.95